2019
DOI: 10.3390/ma12244238
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Activated Titania and Its Application to Photoelectrocatalytic Hydrogen Peroxide Production

Abstract: Photoelectrochemical cells have been constructed with photoanodes based on mesoporous titania deposited on transparent electrodes and sensitized in the Visible by nanoparticulate CdS or CdS combined with CdSe. The cathode electrode was an air–breathing carbon cloth carrying nanoparticulate carbon. These cells functioned in the Photo Fuel Cell mode, i.e., without bias, simply by shining light on the photoanode. The cathode functionality was governed by a two-electron oxygen reduction, which led to formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The photogenerated electrons which escape recombination are led to the air-diffusion cathode electrode where they participate in oxygen reduction. We have previously found that oxygen reduction by the present PFC is accompanied by substantial hydrogen peroxide production [17]. Therefore, we believe that oxygen reduction in the present case may to a large extent be carried out by the following reaction:…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…The photogenerated electrons which escape recombination are led to the air-diffusion cathode electrode where they participate in oxygen reduction. We have previously found that oxygen reduction by the present PFC is accompanied by substantial hydrogen peroxide production [17]. Therefore, we believe that oxygen reduction in the present case may to a large extent be carried out by the following reaction:…”
Section: Resultsmentioning
confidence: 48%
“…The photoanode electrode was made by depositing a 10 µm nanoparticulate titania film on an FTO electrode and it was sensitized by a combination of CdS, CdSe and ZnS quantum dots. The whole electrode was made by a standard procedure, which has been repeatedly published in the past, for example, in Reference [17]. In short, CdS quantum dots were formed in the mesostructure of titania by successive ionic layer adsorption and reaction (SILAR, 10 cycles), followed by CdSe formation by chemical bath deposition.…”
Section: Construction Of the Photoanodementioning
confidence: 99%
See 1 more Smart Citation
“…However, difficulties in storage and ecological environment transportation of hydrogen persist [13,14]. Liquid fuel reformation is becoming an increasingly important process of hydrogen production for on-board mobile applications [15,16]. The use of bioethanol in the schemes of thermochemical recovery of heat contained in exit flue gases is also an option that was considered [17].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitization of mesoporous Titania films by nanoparticulate CdS and CdSe, in combination with ZnS passivation was used by T. S. Andrade et al [15] for the fabrication of ZnS/CdSe/CdS/TiO 2 /FTO photoanodes, enabling broad visible light harvesting. These photoelectrodes combined with a Pt-free counter electrode, made of carbon cloth with deposited nanoparticulate carbon, were used for the assembly of a photoelectrochemical cell operating as a Photo Fuel Cell, i.e., without any external bias.…”
mentioning
confidence: 99%